Progression of Alternaria blight of mustard in relation to components of resistance - S.J. KOLTE, BRAJESH KUMAR and (Indian Phytopathology, 2002)
Progression of Alternaria blight disease (Alternaria brassicae) in nine genotypes of mustard in relation to different resistance components, viz., number of spots, size of spot, sporulation, disease index, apparent infection rate, area under diseaSe progress curve (AUDPC), leaf defoliation and their effect on yield potential were studied under field conditions for two consecutive years 1997-98 and 1998-99. All the components of resistance were correlated significantly positivewith each other. The yield potential was correlated significantly negative with all the components except with leaf defoliation. The genotypes PR-8988 and PR-9024 showed significantly reduced number of spots (4.36 - 15.89), smaller size of spot (2.12 - 6.17 mm), lower sporulation (0.30 - 1.84 x 103 conidia), lower disease index (36.51-42.20%), reduced apparent infection rate (r = 0.047-0.080), lesser values of AUDPC (45.35-126.70) on leaf and pod respectively alongwith reduced leaf defoliation (38.40-44.40%) in comparison to national susceptible genotype Varuna. Therefore these genotypes showed higher degree of partial resistance or slow blighting. The development and progression of Alternaria blight was slower in the case of above two genotypes in comparison to the others used in the study. Genotypes RR-9301 and PR-9650 showed high degree of susceptibility to the disease, development and progression of Alternaria blight on them was faster than on Varuna. The yield (q ha’) of the genotype Kranti was highest (14.01) followed by genotype PR-9024 (11.14). But the yield day" was highest in genotype Divya (11.12 kg ha day") in comparison to the others